Relationship between leadership styles employee commitment and business performance : a study of black top managers in state-owned enterprises - Eresia-Eke, Chukuakadibia E. (University of Pretoria, 2018)
The aim of this study is to investigate the relationship between the leadership styles of black top managers, employee commitment and business performance in state-owned enterprises. With the transformation policies implemented in a post-democratic South Africa, the appointment of black managers into top management positions, in state-owned South African organisations, came with negative connotations and stereotypes attached to African leadership. These connotations have led to a concern about the ability of black managers to provide effective leadership in organisations. Whilst it is critical to appreciate that the business performance of an organisation is influenced by a cocktail of factors, indeed, leadership capability is often primarily questioned when strategic objectives are not achieved. It is for these reasons that the objective of this study sought to identify the prevalent leadership styles displayed by black top managers and to determine if these styles have any association with employee commitment and the business performance of State-owned Enterprises (SOEs). The study also explored the possible role of span of control in moderating the relationship between leadership styles and employee commitment. The study is grounded on the positivism philosophy. A deductive approach was employed to formulate the hypotheses so as to respond to the objectives of this study. A non-probability sampling method, specifically the judgemental sampling technique, was used to select black top managers in the SOEs. A survey method was employed to collect primary data in a cross-sectional manner from 232 direct reports of 38 black top managers in the state-owned enterprises in South Africa. The information collected was complemented by secondary data about the span of control of black top managers and the business performance of their units. Statistical analysis of collected data revealed that respondents perceived black top managers to predominantly display a transformational leadership style coupled with a contingent reward facet of the transactional leadership style. It was also observed that the transformational leadership style displayed a relationship with the affective commitment of employees. The study also found that as the span of control increases, the management by exception (Active) facet of transactional leadership style moderates the relationship between leadership style and organisational commitment. The findings of this study contribute to the building of a body of knowledge on African leadership within the context of management literature. This is owing to the fact that it provides invaluable insight to the leadership behaviour displayed by black top managers in SOEs within a South African context. While caution on attempts to generalise the study’s findings is necessary, in the studied population, top managers in South African SOEs and indeed their organisations may benefit from displaying a transformational leadership style as it lends itself to employee commitment. Further, the study also provides insights on moderating effect that span of control has in the mix of leadership style and employee commitment. The study contributes to theory and practice in the territory of leadership in an African context by highlighting the predominant usage of the transformational leadership style among black top CEOs in SOEs in South Africa, perhaps owing to the societal premium placed on the unique Ubuntu notion in South Africa. Besides this, the study also empirically demonstrates the link between the Management by Exception facet of the transactional leadership style and the affective commitment of employees. The implication of this finding is that black top managers SOEs that invest in the development practices coincident, particularly when spans of control are high, can engender levels of commitment in their employees that would prove beneficial to the organisation.